2017
DOI: 10.1113/jp273189
|View full text |Cite
|
Sign up to set email alerts
|

Post‐translational cleavage of Hv1 in human sperm tunes pH‐ and voltage‐dependent gating

Abstract: In human sperm, the voltage-gated proton channel Hv1 controls the flux of protons across the flagellar membrane. Here, we show that sperm harbour Hv1 and a shorter isoform, termed Hv1Sper. Hv1Sper is generated from Hv1 by removal of 68 amino acids from the N-terminus by post-translational proteolytic cleavage. The pH-dependent gating of the channel isoforms is distinctly different. In both Hv1 and Hv1Sper, the conductance-voltage relationship is determined by the pH difference across the membrane (∆pH). Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 43 publications
2
89
0
Order By: Relevance
“…Remarkably, 3D-STORM images showed that Hv1 forms the bilateral, and not the quadrilateral, lines along the PP (Figures 1E and 1F; Figure S2), and such localization was preserved upon sperm in vitro capacitation (Figure S3A). It has been reported that, during sperm final maturation (also known as capacitation), Hv1 channels undergo N-terminal cleavage (Berger et al, 2017); however, its distinct bilateral distribution pattern upon capacitation does not change (Figures S3B and S3C). Such bilateral distribution of Hv1 clearly differs from the quadrilateral arrangement of the murine and human CatSper (Figure S3D; Chung et al, 2014, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, 3D-STORM images showed that Hv1 forms the bilateral, and not the quadrilateral, lines along the PP (Figures 1E and 1F; Figure S2), and such localization was preserved upon sperm in vitro capacitation (Figure S3A). It has been reported that, during sperm final maturation (also known as capacitation), Hv1 channels undergo N-terminal cleavage (Berger et al, 2017); however, its distinct bilateral distribution pattern upon capacitation does not change (Figures S3B and S3C). Such bilateral distribution of Hv1 clearly differs from the quadrilateral arrangement of the murine and human CatSper (Figure S3D; Chung et al, 2014, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…One candidate for H + extrusion in human sperm is Hv1, which moves H + unidirectionally toward the extracellular space and raises the intracellular pH (Ramsey et al, 2006; Sasaki et al, 2006). Hv1 is expressed in human sperm (Berger et al, 2017; Lishko et al, 2010), where it can trigger intracellular alkalization, ensuring a favorable condition for activation of the pH-sensitive CatSper (Kirichok et al, 2006). The resulting Ca 2+ influx directly affects axonemal function and triggers hyperactivation and, perhaps, rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, both sperm species display rheotaxis and undergo rolling, suggesting that also the quadrilateral flagellar architecture along with potential asymmetric cytosolic Ca 2+ gradients established by this structure is dispensable. Furthermore, mouse sperm lack Hv1 channels (Lishko et al , ; Berger et al , ), indicating that asymmetrical, spatially confined pH gradients established by Hv1 are not required for rolling and rheotaxis. Altogether, our results strongly support the concept that passive biomechanical and hydrodynamic processes enable rolling and rheotaxis rather than active spatio‐temporally confined Ca 2+ and H + signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the inventory and regulation of signaling molecules are different among mammalian sperm (Kaupp & Strünker, ). For example, mouse sperm lack Hv1 channels (Lishko et al , ; Berger et al , ), and human CatSper is activated by nanomolar concentrations of prostaglandins and progesterone (Lishko et al , ; Strünker et al , ) that do not activate mouse CatSper (Lishko et al , ). Thus, if the quadrilateral arrangement of CatSper and its control by pH i were key to rolling and rheotaxis of mouse and human sperm, the underlying mechanisms ought to be vastly different.…”
Section: Introductionmentioning
confidence: 99%
“…Important physiological effects of Hv1 on cytosolic pH have also been demonstrated during histamine release by human basophils [17,18] and in sperm where it contributes to capacitation and motility [17,18]. In mammals, only a single gene codes for HV1 although the channel protein may be truncated in sperm and in chronic lymphocytic leukemia through post-translational processing [19,20] HV1 protein expression was reported in certain types of breast cancer cells and inhibition of the channel expression by siRNA or shRNA was found to reduce migration, lower the release of matrix metalloproteinase enzymes and produce smaller tumors in a mouse model [21]. A follow-up clinical study showed a correlation between the expression levels of HV1 and worse prognosis, lower recurrence-free survival and poor disease scores [22].…”
Section: Introductionmentioning
confidence: 99%